Selected visual parameters related to the working conditions of musicians - Pyżalska, Paulina; Głowacka-Sobotta, Arleta; Matthews-Brzozowska, Teresa; Miśkowiak, Bogdan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
Professional musicians are required to practice playing instruments for long hours, which often exerts significant impact on their health. Attention should be given to the specificity of playing each instrument, including uncomfortable and sustained body position and repetitive movements causing long-term strain of certain parts of the body. The aim of this study was to evaluate the impact of long-term playing wind and string instruments on the visual system. Ninety male and female subjects aged 15 to 30 years were included in the study and divided into two groups: musicians (Msc) and non-musicians (nMsc). Significantly less subjects in the Msc group had properly corrected vision, wore optical prescription recommended by an ophthalmologist/optometrist, and/or underwent any eye examination at all in their lifetime, even though more subjects in this group experienced certain asthenopic symptoms. Also, accommodative amplitude got statistically worse under dim illumination conditions, accommodative facility was significantly different between musicians and non-musicians, although there were no differences between the groups when tested in bright illumination. None of the music stands used by the study subjects met the respective standards concerning uniform illumination rates. Playing string and wind instruments is a challenge for the visual system due to the forced body and head positions, and asymmetry between the visual plane and the plane of regard as well as non-uniform illumination in the working environment. However, conditions such as correct working distance and proper tilt of the music stand may be beneficial to the visual system. It is the role of optometrists to properly educate their patients about the importance of appropriate vision correction, especially in dim light and under adverse working conditions and to communicate the impact of such conditions on the visual system.
Optica Applicata, Vol. 52, 2022, nr 1, s. 37-49
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; musicians; visual parameters; working conditions